Investigation of Parameters Affecting Rotational Behavior of Cold-Formed Steel Connection - Krittiya Pawanithiboworn; Tanyada Pannachet; Maetee Boonpichetvong (Salehan Institute of Higher Education, 2023)
This study aims to understand the behavior of connection, which holds an important key to efficient designs of the cold-formed steel structure. The focus is on examining parameters that affect the rotational stiffness and behavior of the cold-formed steel connection made of single-lipped channel sections with a bolt and gusset plate system. The numerical study has been conducted using component-based finite element analysis, with the studied parameters including bolt diameters, number of bolts in the group, size of the bolt group, thickness of the cold-formed steel cross-section, and thickness of the connecting plate. The effect of the variables is evaluated and explained by comparison. The result of the study reveals that the rotational behavior of the connection depends on the details of the assembly. For the given base connection, the parameters that give the greatest effect on the rotation stiffness and the moment capacity are the number of bolts and the bolt diameters, whereas the parameter that provides the least effect is the bolt spacing. On the other hand, the bolt group size is the most influential parameter for the member connection. For both types of connections, the thickness of the cold-formed steel section and the thickness of the gusset plate have shown limited effect on stiffness and strength. Using different variables in assembling the connection can also lead to different failure types, either bolt failure or excessive bolt hole deformation, which leads to plate failure. Doi: 10.28991/CEJ-2023-09-11-08 Full Text: PDF